2018
DOI: 10.3390/genes9040188
|View full text |Cite
|
Sign up to set email alerts
|

UBE2C Is a Transcriptional Target of the Cell Cycle Regulator FOXM1

Abstract: FOXM1 (forkhead box protein M1) is a transcription factor that participates in all stages of tumor development, mainly through the control of cell cycle and proliferation, regulating the expression of genes involved in G1/S and G2/M transition and M phase progression. The ubiquitin conjugating enzyme E2 (UBE2C) is a member of the anaphase promoting complex/cyclosome, promoting the degradation of several target proteins along cell cycle progression, during metaphase/anaphase transition. FOXM1 and UBE2C have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…Western blot analyses were performed as previously described 66 . The primary antibodies used were: anti-Cebpd #7077 (ProSci, Poway, CA, USA); anti-Fos sc-166940 (Santa Cruz Biotechnology, Dallas, TX, USA); anti-Bcl2l1 #2762 (Cell Signaling, Danvers, MA, USA).…”
Section: Western Blotmentioning
confidence: 99%
“…Western blot analyses were performed as previously described 66 . The primary antibodies used were: anti-Cebpd #7077 (ProSci, Poway, CA, USA); anti-Fos sc-166940 (Santa Cruz Biotechnology, Dallas, TX, USA); anti-Bcl2l1 #2762 (Cell Signaling, Danvers, MA, USA).…”
Section: Western Blotmentioning
confidence: 99%
“…In addition, we found that UBE2C mRNA expression levels were high in certain triple negative cell lines. Nicolau-Neto et al reported that UBE2C is a transcriptional target of the cell cycle regulator FOXM1, which was identified as a specific marker for TNBC (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the expression of UBE2C, TTK, and TPX2 is involved in ESCA pathology and prognosis. As a ubiquitin-conjugating enzyme, UBE2C promotes the degradation of several cell cycle-regulated proteins that control progression through mitosis [ 55 ]. Knockdown of UBE2C significantly inhibits cell proliferation via cell-cycle regulation, in in-vitro ESCA cell models, particularly in TE-1 cell lines [ 56 ].…”
Section: Discussionmentioning
confidence: 99%